Zikir Sufi dalam Studi Wacana dan Budaya - Hasanuddin Chaer; Syamsinas Jafar; Mari'i Mari'i; Aswandikari Aswandikari; Mahmudi Efendi; Murahim Murahim (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2023)
This article presents discourse texts in Sufism culture, especially about the meaning of dhikr and the spiritual values inherent in Sufi discourse texts. For this reason, researchers are trying to explore the concept of dhikr of the Tarekat Sheikh through a discourse study approach. This is because every living and healthy dhikr has its own special features which lie in its special message in the bias of revelation through culture and life. Researchers try to offer the concept of Sufi dhikr of Sheikh Ahmad Tet, considering that the tradition of dhikr is a reflection of Islamic culture. The aim of this research is to explore the meaning of the word dhikr through expressions in the manuscript of the book 'Secrets of Bainal Haq', as a form of discourse text that supports social-spiritual relationships.To understand this, researchers used Foucault's theory of discourse study, with analytical descriptive methods. The steps that researchers took were data collection, data processing, and interpretation of research data, which results in understanding the words and meaning of Sufi discourse texts. Therefore, the results of this research reveal that Sufi dhikr has similarities in social-spiritual values, a balance between the dimensions of faith and shari’ah, the dimensions of knowledge and worship, the dimensions of culture and morals, and the dimensions of language and culture which is the representation of religious culture traditional practices.